Risk analysis of waterlogging in a big city based on a bow-tie Bayesian network model, using the megacity of Wuhan as an example - Li, Jiao; Liu, Juan; Wu, Tiancheng; Peng, Qianxi; Cai, Chun (Frontiers in Environmental Science, 2023)
At present, the global urbanization process is accelerating, with climate changing constantly and extreme weather increasing. Under this background, urban flood disasters caused by rainstorm frequently occur in China. Therefore, a disaster risk analysis model based on Bow-tie Bayesian network is established to analyze the risk of waterlogging disasters. Firstly, analyze the waterlogging accident, identify the intermediate and basic events that caused the accident, and draw the accident tree. According to the intuitive nature of the fault tree, it is transformed into a Bayesian network, and in the meantime, a posteriori probability analysis of nodes is performed to further obtain the critical importance of basic events. By analyzing the importance of basic events of waterlogging disasters, the key basic events that lead to disasters are proposed. Finally, analyze the importance of its hazards with the Bow-tie model, and propose prevention and control of accidents. The results show that the major accident node of urban waterlogging accidents is the unsafe state of the urban environment, and the management and control of the urban environment should be strengthened to improve the prevention and control of urban waterlogging from aspects such as pre disaster prevention.